Finite and Infinite Intellect: Salomon Maimon’s Resolution to Kantian Antinomies - Pelegrin, Laura Alejandra (2025)
This paper examines the central role of antinomies in Salomon Maimon’s philosophy. The problem of antinomies occupies a prominent place in the philosophy of Maimon. Historically, the antinomies of reason constitute a problem to which Maimon must give an answer, since it is one of the nuclei of discussion that is generated in his correspondence with Kant. In relation to the systematic perspective, Maimon has modified the way in which several of the dichotomous pairs proper to Kantian philosophy are related, i.e., intuition-concept, formmatter, sensibility-understanding. The antinomies were one of the arguments that led Kant to conclude that intuitive and conceptual representations come from heterogeneous sources. Maimon accepts that there are antinomies of reason. Then, Maimon has to explain how, even with the suppression of the heterogeneity of faculties, the antinomic conflict can be resolved. Within the framework of this problem, the general aim of this paper is to analyse the way in which Maimon reformulates the Kantian antinomies. In particular, we aim to study the new formulation and resolution of the antinomies. We will argue that the distinction between finite and infinite intellect, which provides a resolution to the antinomy, must be interpreted in relation to the distinction between reason and imagination.